Pengaruh biaya produksi, biaya kualitas, dan biaya pemasaran terhadap laba bersih pada perusahaan manufaktur sub sektor makanan dan minuman yang terdaftar di Bursa Efek Indonesia Tahun 2022-2023 - Warbung, Kasih Michelly Kesya; Pontoh, Winston; Latjandu, Lady Diana (Yayasan Widyantara Nawasena Raharja, 2025)
This study aims to analyze the effect of production costs, quality costs, and marketing costs on net profit in food and beverage manufacturing companies listed on the Indonesia Stock Exchange during 2022–2023. The research is motivated by the need to understand how efficient cost management serves as a signal of corporate performance in the post-pandemic recovery period. Using a quantitative associative approach with multiple linear regression analysis, the study utilizes secondary data from audited annual financial statements of 116 firm-year observations. The results reveal that quality costs and marketing costs have a significant positive effect on net profit, while production costs show no significant effect. Simultaneously, all three cost variables significantly influence net profit. These findings indicate that strategic allocation of quality and marketing expenditures strengthens profitability and provides a positive signal to investors regarding the company’s financial performance. This study contributes to the cost management and signaling theory literature by empirically demonstrating the importance of efficient cost structure in enhancing firm profitability and market perception.